Career changers in teaching jobs: A case study based on the Swiss vocational education system - Stefanie Hof; Mirjam Strupler; Stefan C. Wolter (Institute for the Study of Labor (IZA), 2011)
This study investigates the determinants and motives of professionals who change career to vocational teaching. The framework for this study is the Swiss vocational education system, which requires that teachers of vocational subjects must have a prior career in that specific field. Thus, to work in teaching, every vocational teacher has to change his or her initial career. This paper focuses on the relevance of monetary motives for changing a career to teaching. Using a unique data set of trainee teachers, we show that professionals who change their careers to teaching earned on average more in their first career than comparable workers in the same occupation. Our findings additionally demonstrate that the average career changer still expects to earn significantly more as a teacher than in the former career. However, the study shows substantial heterogeneity and a zero wage elasticity of the teacher supply, suggesting that non-monetary motives are more relevant for career change than monetary factors.
urn:nbn:de:101:1-20110629941
Keywords: C21; I20; J24; J45; J62; 330; career change; occupational change; rate of return to education; wage differentials; teacher wages; vocational education and training